185k views
2 votes

4b + 3 = - 9


User Aherman
by
5.4k points

2 Answers

2 votes
Answer: b= -3

Let’s rewrite the equation

4b+3=-9

To solve for b, we need to first work to isolate it. To get 4b alone on the left side, let’s subtract 3 on both sides.

4b+3=-9
-3 -3
_______
4b=-12

Now we need to finally get b by itself. Since it is being multiplied by 4, we’ll undo this with division. Let’s divide 4b and -12 by 4.

4b= -12

4b/4= -12/4

b=-3

This is your answer! Hope this helps comment below for more questions :)
User Masrtis
by
4.8k points
5 votes
move both constants to the right than change the sign

4b=-9-3

then calculate -9-3 which is -12
now we have 4b=-12

now we isolate 4 by dividing both sides of the equation

4b= -12

which is

b= -3


so no
User Simon Wilson
by
5.0k points